Extraction of plant protein and solanesol from tobacco leaves process plant feasibility study and design for the Philippine setting - De Chavez, Reynaldo C. Jr; Japitana, Paulene
The proposed plant plans to extract protein and solanesol from tobacco leaves. This is primarily motivated by the supposed high quality of tobacco protein and the emerging applications and increasing demand for solanesol. Another reason is the health hazards brought about by the products made from tobacco and the effects of the recent Sin Tax Bill on local producers of the crop. Market study has been performed to examine the feasibility of this plant. Examining the products, raw materials and economic dynamics, the market could be considered a high-risk investment. The proposed plant aims to be an intrinsically safe and environment-friendly plant with minimized waste production. It also operates in batch and in small-to-medium scale. The process designed is mainly a separation process and only make use of the tobacco leaves as the raw material.Due to the high cost of production and resulting negative profit, the project is not feasible at the moment. At a small scale, the costs are just too high, particularly in the purchase of equipment. The cost of equipment is not maximized due to their capacity exceeding what is required by the process, thus under utilizing the machines. Through further maximization of the process efficiency and technology development for production at a lower cost and higher revenues, and with possible incentives from the government and support from pharmaceutical companies, the project could become feasible.